Impact of Entrepreneurial Capability on New Product Development and Marketing Performance - Lewa, Andi Hallang (Jurnal Penelitian Ekonomi dan Bisnis, 2022)
This study departs from the problem of empirical contradictions in the findings of the study of the relationship between entrepreneurial capability and business performance. This study aims to examine and analyze the effect of Entrepreneurial capability on New Product Development which has an impact on Marketing performance. The population of this research is batik UMKM which is listed in the Map Report of the Batik Industry of the Industry and Trade Office of Central Java Province in 2013 and has criteria in accordance with the Law of the Republic of Indonesia no. 20 of 2008 non-exporter which refers to the distribution data of the number of SMEs in Central Java batik. The unit of analysis that will be used as respondents in this study is the owner or manager or owner and manager of batik SMEs in 3 (three) major areas of Central Java, namely Semarang, Pekalongan and Surakarta as many as 364 respondents. The analysis technique used in this study is Structural Equation Modeling. (SEM) with the AMOS/Amos Graph program. The results of the study indicate that the entrepreneurial capability has a positive and significant effect on new product development and marketing performance and new product development has a positive and significant effect on marketing performance.